Valuing landscape identity of local inhabitants through a tourism discourse - Eetvelde, V.V. (2017)
Landscape, people and identity Landscape is about the interaction of a place or an area with people, which is reflected in the material interaction of people creating or shaping the landscape as well as in their mental perception, valuation and symbolic meaning of that landscape (Cosgrove 1998). This mutual and dynamic interaction forms the fundamental principle of the concept of landscape identity. Landscape identity has been described in scientific literature as a concept to bridge the physical, social and cultural aspects of landscapes. Also policy documents related with landscape and heritage (for example the UNESCO World Heritage Convention, the European Landscape Convention, the Faro Convention) are mentioning identity and landscape as key concepts. In those examples, landscape identity can refer to either the landscape itself - its features that makes the landscape unique (thus the landscape character), or to the social and personal construction. However, there is an interdependency between those two perspectives that needs to be conceptualised. Landscape identity is therefore defined as the multiple ways and dynamic relation between landscape and people (Loupa Ramos et al 2016).